EFEKTIVITAS METODE EVERYONE IS A TEACHER HERE DALAM MENINGKATKAN MINAT PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS V MADRASAH IBTIDAIYAH AL ZAYTUN - Nur Afifah, Fadiyah; Kartini; Humaeroh, Iis (Cahaya Ilmu Bangsa Institute, 2024)
This research was conducted because, in the Islamic Cultural History lessons, the teacher explained the material in a monotonous manner, using the lecture and assignment methods. These methods, which are considered monotonous, affected students and resulted in a lack of active participation during the learning process. Consequently, the material delivered did not leave a lasting impression that could influence students' interest and learning outcomes. Given this problem, the researcher attempted to improve the learning process of Islamic Cultural History by applying the